Nanotechnology Enhancing Silk Production and Quality Through Nanoparticle Interventions: Sericultures Latest Development - Doddananjaiah, Prathibha Hampapura; Manjunatha H B; Gurusiddappa, Lingaraju Honnur; Charan Kumar Kachintaya; Sushma Shree Krishnappa (The Bioscan, 2024)
Sericulture, the art of making silk, is essential to many sectors because it produces high-quality silk, biomass, silk protein, and animal feed. The development and creation of cocoons by silkworms, which predominantly rely on mulberry leaves as a food also these are crucial to the success of silk manufacture. Over the past few decades, several studies have been initiated to explore the possible applications of nanotechnology as a viable means of improving sericulture. A significant improvement in the quality of silk fibers produced can be attributed to the incorporation of nanotechnology into sericulture practices, which has shown promising results in terms of improving silkworm survival, encouraging growth and development, and improving cocoon weight and length. Additionally, nanotechnology can dramatically alter the way silk is produced by boosting the synthesis of fibroin, which has farreaching effects on industries like bioengineering and biomedicine. In addition to improving silk fiber quality, enhanced fibroin production also creates new opportunities for the creation of cutting-edge biomaterials and biological applications. This paper seeks to examine the effects of nanoparticles on several characteristics of sericulture, including the weights of mature silk glands, pupae, cocoons, cocoon shells, and the contents of fibroin and sericin. The use of nanotechnology in sericulture has greatly aided developments in several fields, and its application in this sector continues to draw interest and funding.